2018
DOI: 10.1097/ceh.0000000000000197
|View full text |Cite
|
Sign up to set email alerts
|

A Guide for Planning and Implementing Successful Mental Health Educational Programs

Abstract: These results will be helpful for planning and improving the quality of future educational programs in mental health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 82 publications
0
1
0
2
Order By: Relevance
“…Esperava-se que a adoção de elementos já apontados como importantes para o sucesso de programas educacionais em saúde mental, como metodologias ativas de ensino-aprendizagem, abordagem de temas e conteúdos relacionados à prática diária do treinamento dos estudantes e envolvimento de docentes especialistas tanto na elaboração quanto na execução do programa 8,15 , fossem suficientes para produzir ganhos nas duas dimensões.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Esperava-se que a adoção de elementos já apontados como importantes para o sucesso de programas educacionais em saúde mental, como metodologias ativas de ensino-aprendizagem, abordagem de temas e conteúdos relacionados à prática diária do treinamento dos estudantes e envolvimento de docentes especialistas tanto na elaboração quanto na execução do programa 8,15 , fossem suficientes para produzir ganhos nas duas dimensões.…”
Section: Discussionunclassified
“…Após a exigência da inclusão da saúde mental como área básica nos parâmetros curriculares nacionais dos cursos de Medicina 7 , as escolas médicas estão desde então obrigadas a incluir o treinamento em saúde mental no internato. No entanto, a escassez de publicações sobre a eficácia destas intervenções reforça a importante falha percebida na cultura institucional e educacional em avaliar sistematicamente a eficácia dos programas educacionais 8 .…”
Section: Introductionunclassified
“…In their extensive review of the continuing education literature within the health professions, the Institute of Medicine (2010) reported that over 90% of the professional development programs were didactic in nature. Likewise, in their review of the mental health field, Blanco-Vieira and colleagues (2018) noted that “lecturing was used as the main teaching tool in 78% of the studies reviewed” (p. 133).…”
Section: Continuing Education Memesmentioning
confidence: 99%